Show to tell: a psychoanalytic reflection on photography as a tool for unconscious storytelling in personal and clinical practice - Zadok, Maorr (The University of Edinburgh, 2024)
In this thesis, I invite you to join me on a journey, told in photographs and shown through words, into the realms of my reflexivities in an attempt to explore new ways that reflexive practices can be used as a means for personal and professional development in counselling and psychotherapy. While there have been many discussions into the use and importance of reflectivity as a tool for personal and professional development within the field of counselling and psychotherapy (McLeod, 1999, 2006; Rose, 2011, 2018; Sanders et al., 2021), I present through this thesis that to simply reflect – that is, to bounce back – is not enough. Instead, I propose that trainee and qualified counsellors and psychotherapists should be encouraged to develop a diverse range of reflexivities (Serra Undurraga, 2020a) – ways of bending backwards and inwards – that not only question the source of a feeling or experience, but also examine the ways in which these questions are being asked. This thesis is the product of an inquiry into the need to develop personal and unique understandings of, as well as methods of engagement with, reflexivity. Deriving from my own practice of using photography as a method of engagement with my reflexivities, this thesis seeks to explore, without presenting formal conclusions or universal claims, ways of answering the following questions: does a photograph itself hold the capacity to offer a reflexive space on its own, or does it require language to be able to hold itself as a formally reflexive practice? How might photography, as a reflexive practice, assist us as psychotherapy trainees and practitioners in exploring and understanding ourselves and our Unconscious better than we would otherwise? Is photographic theory and practice able to align itself to psychoanalytic theory and practice and how might it assist in developing an individual’s capacity for reflexivity? At the core of my attempts to explore potential answers to the above questions is a unique post qualitative (St. Pierre, 2019) methodology that seeks to illuminate what happens when we think without method (Jackson, 2017): reflexivity-in-practice. Utilising an onto-epistemological (Barad, 2007) stance of immanence, performativity, and production, this thesis diffracts (Barad, 2007) the various intra-actions (Barad, 2003) between Freudian and Lacanian psychoanalysis and photography through the perspective of critical posthumanism (Braidotti, 2019) in order to explore how they can be aligned to create a new form of reflexivity: latency. By combining latent reflexivity with four other aspects of reflexivity – diffraction (Barad, 2007), mastery, foreignness, and performative meta-reflexivity (Serra Undurraga, 2020a) – I present a new version of performative meta-reflexivity that has both been produced by and producing from my reflexivity-in-practice methodology. The key product of the methodology shown in this thesis is my personal reflexive photography, taken throughout my time as a trainee as well as whilst writing this thesis. These photographs are presented, along with several pieces of reflexive writing, in order to show the ways that they have come to influence, and be influenced by, my reflexive practice. These photographs bring into focus potential answers to the questions presented at the outset through placing a focus on the latent aspects of my reflexivity. The insights and explorations of these diffractive, post qualitative inquiries lead me to present a conclusion that for myself, and potentially others who experience difficulties in using language to fully or sufficiently express or engage with their reflexivities, photography is an inherently psychoanalytic, reflexive tool. Photography, when engaged in reflexively, can be seen as equal to, if not above, the world of language. Photographs hold within themselves a world full of life and history that does not need to be verbally articulated, but instead recognised for the wealth of knowledge that they possess. As such, photography can be used as a reflexive tool to guide psychotherapy trainees and practitioners further into their journey of personal and professional development, and perhaps show something that their words would otherwise be unable to.
Keywords: Psychotherapy; Reflexivity; Photography; Psychotherapy; Psychoanalysis; Diffraction; Post qualitative inquiry; Posthumanism; Freud; Lacan; Personal Development; Professional Development; Counselling; Counselling and Psychotherapy; Counselling and Psychotherapy Training; Reflexive Practice; Reflectivity